2020
DOI: 10.3390/vaccines8030365
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Inner Capsid VP6 Acts as an Adjuvant in Formulations with Particulate Antigens Only

Abstract: Novel adjuvants present a concern for adverse effects, generating a need for alternatives. Rotavirus inner capsid VP6 protein could be considered a potential candidate, due to its ability to self-assemble into highly immunogenic nanospheres and nanotubes. These nanostructures exhibit immunostimulatory properties, which resemble those of traditional adjuvants, promoting the uptake and immunogenicity of the co-administered antigens. We have previously elucidated an adjuvant effect of VP6 on co-delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…( A ) Different expression systems from prokaryotic E. coli [ 2 , 72 , 126 ] to eukaryotic systems such as yeast [ 17 ], insect cell/baculovirus systems (IC-BV) [ 38 , 67 ], mammalian cells [ 38 ], HSV-1 [ 90 ], and plant cells [ 37 , 89 , 127 ] have been used successfully to produce assembled structures of VP6 tubes/VLPs. ( B ) Applications of VP6 tubes/VLPs, as vaccines (immunogenicity and protection) [ 15 , 44 , 54 , 55 , 64 66 , 70 , 95 , 108 ], adjuvants [ 15 , 16 , 55 , 76 78 , 108 – 110 ], immunological carriers [ 49 , 53 , 92 , 96 , 102 , 111 ], drug delivery tools [ 5 , 91 , 122 , 126 ], and nano-biomaterials [ 5 , 23 , 24 , 41 , 42 , 50 , 91 , 122 , 126 ] …”
Section: Vp6 Expression and Formation Of Structured Vp6 Tubes/vlpsmentioning
confidence: 99%
See 1 more Smart Citation
“…( A ) Different expression systems from prokaryotic E. coli [ 2 , 72 , 126 ] to eukaryotic systems such as yeast [ 17 ], insect cell/baculovirus systems (IC-BV) [ 38 , 67 ], mammalian cells [ 38 ], HSV-1 [ 90 ], and plant cells [ 37 , 89 , 127 ] have been used successfully to produce assembled structures of VP6 tubes/VLPs. ( B ) Applications of VP6 tubes/VLPs, as vaccines (immunogenicity and protection) [ 15 , 44 , 54 , 55 , 64 66 , 70 , 95 , 108 ], adjuvants [ 15 , 16 , 55 , 76 78 , 108 – 110 ], immunological carriers [ 49 , 53 , 92 , 96 , 102 , 111 ], drug delivery tools [ 5 , 91 , 122 , 126 ], and nano-biomaterials [ 5 , 23 , 24 , 41 , 42 , 50 , 91 , 122 , 126 ] …”
Section: Vp6 Expression and Formation Of Structured Vp6 Tubes/vlpsmentioning
confidence: 99%
“…In this context, it was shown that despite higher induction of the cytokine IL-4 by co-administration of VP6 tubes with norovirus VLPs than with VP6 VLPs, both of these oligomeric VP6 assemblies exerted a similar dose-dependent adjuvant effect on norovirus-specific Ab responses [ 77 ]. More-recent studies have indicated that the particulate nature and size of the co-administered Ag might also affect the adjuvant effect of VP6 VLPs [ 55 ]. In this context, co-administration of VP6 VLPs with either a 20-nm norovirus P particle or a 23-mer extracellular domain of matrix protein M2 (M2e, a monomeric peptide, ~3 kDa) of human influenza A virus showed an adjuvant effect of VP6 VLPs only, enhancing Ab and T-cell immune responses against the preceding Ag (norovirus P particle), and not M2e [ 55 ].…”
Section: The Adjuvant Role Of Rv Vp6 Tubes/vlpsmentioning
confidence: 99%
“…When the VP6 nanotubes were vaccinated with noroVLP or Coxsackie VLP (di or tri-valent) as a combination vaccine, robust protective immunities were induced against both rota and Coxsackie, which also served as an immune modulating effect on VP6 nanotube [ 32 33 34 35 36 ]. On the other hand, recent studies have shown that VP6 nanotube does not exhibit adjuvant characteristics for monomeric antigens or short peptides [ 37 ]. Two types of small antigens, P particles derived from norovirus capsid protein and small peptides (23 mer) derived from extracellular matrix protein (M2e) of influenza virus were tested to demonstrate that VP6 nanotube had an immune supporting effect.…”
Section: Non-replicating Virus-like Particles Vaccinesmentioning
confidence: 99%
“…However, neither M2e peptide alone nor combination with VP6 nanotubes showed significant differences in serum IgG levels. This means that the immune modulating effect of VP6 nanotubes is only effective for antigens in particle form [ 37 ].…”
Section: Non-replicating Virus-like Particles Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation